Proteomic and metabolomic integration of Eucalyptus grandis X Eucalyptus camaldulensis Bark to analyze photosynthetic metabolism and its impact on growth - Gois, Andressa Fernanda Ducatti de (2025)
Eucalyptus is a fast-growing tree that is widely used in the forestry sector due to its adaptability to different climatic conditions and the properties of its wood. Although photosynthesis is crucial for plants, the role of cortical photosynthesis, glycolytic and fermentative metabolism in the secondary growth of eucalyptus trees is not well known. Fast- growing trees, such as eucalyptus, can suffer oxygen shortages in summer due to the high metabolic demand and low permeability of the bark, with an impact on respiration and seasonal carbon allocation. The clone of the hybrid E. grandis x E. camaldulensis (COP 1277) is widely used in integrated crop-livestock-forest (iCLF) systems in Brazil due to its compact canopy, having been developed by Copener Florestal in Bahia, is adapted to water deficit environments and has high-quality wood. This work will look at the impact of sunlight on the eucalyptus stem on cortical photosynthesis and ethanolic fermentation and, consequently, on secondary growth, analyzing proteins, metabolites and the integration of these omics. Cortical photosynthesis occurs in the bark of evergreen trees, where chlorophyllrich cells capture light to convert CO2 and water into sugars, similar to leaf photosynthesis. However, the CO2 gas used comes mainly from stem respiration, helping to regulate its concentration and reducing stress. This type of photosynthesis can recapture 60-98% of the CO2 released by respiration in young trees, contributing to the growth of the trunk, roots and shoots. In addition, it can increase oxygen levels in the cortex, reducing energy crises. The bark cortex contains more chlorophyll and has greater photosynthetic efficiency than other stem tissues, such as the xylem. Plants use two mechanisms for cellular respiration: aerobic respiration and fermentation, depending on the availability of oxygen. Under hypoxia, fermentation occurs, and fast-growing trees, especially in summer, face oxygen shortages due to high metabolic demand and low bark permeability, affecting carbon allocation.